A Proposal on Eco-Friendly Technologies and Green Investment terhadap Corporate Sustainability: The Mediating Role of Business Innovation - Sri Anjarwati; Yolifiandri Yolifiandri; Islamiah Kamil; Ida Royani Damayanti; Ari Apriani (Dinasti Publisher, 2024)
This study aims to test and analyze the influence of Eco-Friendly Technologies and Green Investment on Corporate Sustainability with Business Innovation as a mediating variable in food and beverage companies. Research object is a company engaged in the food and beverage sector in the Jakarta area. The research method used is a quantitative mix method using primary data. Sampling was done using the Purposive sample method. The analysis method used is the equation structure of the WarpPLS model, the result to be achieved is to test the research model.